Malware classification based on target location - Nasuha, Noor Baha (2014)
The combination of Malicious and Software have contribute a phrase call as Malware. Malware are software that is intended to damage or disable computers and computer systems. Malware is software used to disrupt computer operation, gather sensitive information, or gain access to private computer systems. In addition malware will interrupt user on activities by using computer. The processes of classification show that malware need to classify detected objects with antivirus program. The antivirus industry used simple classification methods, comprising a unique name and the size of the detected file. However, a single antivirus could end up being called different names by different antivirus solutions, which can lead confusion. Now days, malicious programs are rapidly increases as well as the advent of new platforms of antivirus. The specific problem that malware has create, now a days there are various type of malware that become difficulty to antivirus to confirm or differentiate what type of malware attack the computer based on their characteristics. There are consists many different type or different characteristics of malware have been created. The goal of this project is to classify malware based on target class. To achieve this goal three objectives need to finish up which are to investigate system directory in window based on platform, to design malware classification system based on identified targeted class and to develop system for classifying malware based on target location. In this paper, problem had been identified and reviewed the existing malware detection. From analysis, other way had been proposed for malware classification based on target location. Output from this framework can be used by system administrator to plan and implement prevention mechanism in order to minimize future malware threat.